Cyclophosphamide Regulates N6-Methyladenosine and m6A RNA Enzyme Levels in Human Granulosa Cells and in Ovaries of a Premature Ovarian Aging Mouse Model - Huang, Boxian; Ding, Chenyue; Zou, Qinyan; Wang, Wei; Li, Hong (Frontiers in Endocrinology, 2019)
Cyclophosphamide (CTX) is one of the most frequently used alkylating anticancer drugs. CTX is associated with reproductive failure and premature ovarian insufficiency (POI) or premature ovarian aging. Much less is known about the mechanism by which CTX affects female fertility through N6-methyladenosine (m6A) levels. In this case-controlled study, we employed human ovarian granulosa cells and mice as experimental models in vitro and in vivo. m6A test kit was developed to determine the content in RNA, and qPCR and western blot were used to examine the expression levels of RNA methyltransferases, demethylases and effectors. Results showed that CTX increased the m6A level in a time- and concentration-dependent manner. The expression levels of RNA methyltransferases were significantly higher in the CTX treatment group than in the control group with time and concentration dependence, except for RBM15 and WTAP. CTX significantly inhibited the expression levels of RNA demethylase FTO in a time- and concentration-dependent manner but not ALKBH5. The expression levels of RNA effectors were reduced by CTX in a time- and concentration-dependent manner. These data suggest that CTX increased the expression levels of m6A and may be responsible for the increase in RNA methyltransferases and decrease in RNA demethylases in a time- and concentration-dependent manner.